2015
DOI: 10.1111/jphp.12410
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of cadherin-11 and β-catenin signalling during proliferation of rheumatoid arthritis-derived synovial fibroblast cells

Abstract: CDH11-mediated β-catenin signalling was 42% involved in IL-1β-induced proliferation and had the highest susceptibility to IL-1β among the proliferative signallings analysed in this study. The mode of action for CDH11 during the cell proliferation was likely associated with a pool of β-catenin protein. In contrast, CDH11 and β-catenin were not involved in TNF-α-induced RA-SFC proliferation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…[41] The authors concluded that CDH11 is involved in IL1β-mediated pathways, and that there is an indirect interplay between the two genes via β-catenin. [41] In a related study, Chang and coworkers demonstrated that CDH11 engagement had strong synergies with IL1β signaling upon interleukin 6 (IL-6) induction in synovial fibroblasts, and that the mitogen-activated protein kinase (MAPK) [c-Jun N-terminal kinase (JNK) and extracellular signal–regulated kinase 1 and 2 (ERK1/2)] and the nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) pathways were activated. [42] Thus, the signaling cascades of IL1β and CDH11 may be related through β-catenin, MAPK, and/or NF-κB in AoAFs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[41] The authors concluded that CDH11 is involved in IL1β-mediated pathways, and that there is an indirect interplay between the two genes via β-catenin. [41] In a related study, Chang and coworkers demonstrated that CDH11 engagement had strong synergies with IL1β signaling upon interleukin 6 (IL-6) induction in synovial fibroblasts, and that the mitogen-activated protein kinase (MAPK) [c-Jun N-terminal kinase (JNK) and extracellular signal–regulated kinase 1 and 2 (ERK1/2)] and the nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) pathways were activated. [42] Thus, the signaling cascades of IL1β and CDH11 may be related through β-catenin, MAPK, and/or NF-κB in AoAFs.…”
Section: Resultsmentioning
confidence: 99%
“…[37, 41, 45] While IL1β has been widely identified as playing a key role in fibroblast proliferation, few studies have implicated CDH11. [41] For example, Vesey et al . found that IL1β was a potent inducer of proliferation with similar activities to those of TGF-β1 in human cortical fibroblasts.…”
Section: Resultsmentioning
confidence: 99%
“…ICAM‐1 and VCAM‐1 expression plays a key role in maintaining inflammation; our study suggests that IL‐21 up‐regulates the expression of ICAM‐1 and cadherin‐11 that may partly interpret the IL‐21‐induced invasion. Cadherin‐11 mediated the β‐catenin signalling involved in IL‐1β‐induced proliferation, but was not involved in TNF‐α‐induced RA‐FLS proliferation . In this study, we found that IL‐21 induced cadherin‐11 expression in RA‐FLS; whether cadherin‐11 mediates IL‐21‐induced proliferation and invasion needs further study.…”
Section: Discussionmentioning
confidence: 61%
“…In another study, CDH11 induced IL-6 production through MAPK signaling or NF-κB activation, and synergized with other pro-inflammatory molecules such as tumor necrosis factor-α (TNF-α) and IL-1β to enhance the expression of these inflammatory mediators [22,25]. Yoshioka et al [26] elucidated the role of CDH11 in TNF-α induced RA-FLS proliferation, which might be a β-catenin library. Moreover, Wu et al [27] found that PI3K/Akt pathway was related to the expression of CDH11 induced by pressure or inflammation, which might be involved in the pathogenesis of arthritis [9].…”
Section: Rheumatoid Arthritis (Ra) and Cdh11mentioning
confidence: 99%